Pathogenic beliefs among patients with depressive disorders - Adam Neelapaijit (2018)
© 2017 Neelapaijit et al. Introduction: Pathogenic belief is a central construct within control-mastery theory, which is an integrated dynamic-cognitive-relational approach in psychotherapy. Pathogenic beliefs result from traumatic life experiences and are considered the root of any psychological disorders presented clinically. Nevertheless, how and what type of pathogenic beliefs are attributed to clinical depressive disorder is unknown. The present study aimed to examine this issue. Patients and methods: Thirty patients with depressive disorder, who came for psychotherapy at a psychotherapy clinic, were matched based on age and gender with healthy controls who were medical students. The 54-item pathogenic belief scale (PBS) was administered and compared between depressive and control groups using odds ratio (OR). Results: The depressed group’s PBS mean score was significantly higher than the healthy controls (t=3.78, P<0.001). Thirteen of 54 items significantly differed between the two groups with ORs ranging from 3.76 to 16.79. The content of pathogenic beliefs centered on the issues of negative sense of self, lack of self-efficacy and control, and relational difficulties related to feelings of fear and humiliation. Influences of culture and gender differences on pathogenic beliefs were discussed. Conclusion: Pathogenic beliefs relate to depression such that the higher the number of pathogenic beliefs one has, the more the likelihood of having depression. Since the PBS was developed based on clinical data (rather than theory based), cultural issues as well as age and gender may influence the development of pathogenic beliefs. Further study should be warranted and implications for clinical practice are discussed.